Web-based learning environments for the vision impaired - Permvattana, Ruchi; Armstrong, Helen; Murray, Iain (IADIS press, 2010)
Many web applications including online learning are not accessible to vision impaired students. This paper presents the details of research in designing accessible online IT learning environments for vision impaired students. The research investigates the features of currently available e-learning environments for the vision impaired, international standards and guidelines and theoretical models relting to accessibility of learning environments. The research aslo involves gathering data from interviews and observations from sighted and vision impaired teachers and students to identify characteristics of a range of vision disabilities and the needs associated with these. Eventually the research will deliver a model of an effective web-based learning environment for the vision impaired, thus providing assistance to those designing and developing such environments as well as the opportunity for vision impaired individuals to better equip themselves for employment. Although still a work in progress, the paper identifies characteristics that are desirable in an e-learning environment that empowers the vision impaired to achieve the course learning objectives.